Comparison over 25 years of the burden of familial hypercholesterolemia on hospitalizations for coronary heart disease in a French-Canadian founder population. (3rd October 2022) - Lauziere, A; Brisson, D; Tremblay, G; Bedard, S; Khoury, E; Gaudet, D
Abstract: Background: Over the last 25 years, effective treatments, such as potent statins, ezetimibe and PCSK9 inhibitors have gradually emerged to treat heterozygous familial hypercholesterolemia (FH) and guidelines have been progressively developed internationally to promote FH health surveillance, early diagnosis and optimal clinical management. However, the impact of these measures on the burden of FH is not well documented. Although recent genetic and epidemiological studies suggest that the prevalence of familial hypercholesterolaemia (FH) is approximately twice than initialy expected (1:250) (1), it remains significantly higher among French Canadians (FC) (2, 3). Purpose: To compare over 25 years the management and burden of FH among patients hospitalized for an acute coronary heart disease (CHD) event in a FC founder population with a high prevalence of FH. Methods: Lipid profiles, cardiovascular risk factors, lipid management and FH status of 2, 029 FC patients consecutively hospitalized for an acute CHD event between 2017 and 2022 (2022 Cohort) were compared to those of 2, 506 patients with angiographically-confirmed CHD who were admitted between 1995 and 1998 (1998 Cohort) (4). FH status was based on molecular, Simon Broome or FH Canada (5) criteria. Statistical comparisons were made using Chi-square and Student's t-tests for independent samples. Results: Over a 25-year interval, most patients hospitalized for CHD were men (74.5% in 1998 vs 73.4% in 2022). At the time of admission, 23.0% of CHD patients had LDL-Cholesterol levels >5.0 mmol/L in 1998 compared to 1.3% in 2022 (p<0.001). FH was diagnosed in 9.6% of patients in the 1998 cohort compared to 5.5% in 2022 (p<0.001). Overall, the prevalence of obesity, type 2 diabetes and uncontrolled hypertension tended to be higher in 1998, including in FH (p<0.05). The proportion of FH patients hospitalized for CHD who were treated with a statin or a combination of lipid-lowering agents at the moment of admission was 28.4% in 1998 compared to 61.2% in 2022 (p<0.001). FH patients hospitalized for CHD were significantly older in 2022 than in 1998 (59.03±11.17 vs 50.14±11.32 years; p<0.001). Accordingly, the prevalence of premature CHD requiring an hospitalization significantly decreased from 1998 to 2022 in FH (64.3% vs. 44.1%, p<0.001). Conclusions: Over a 25-year period, FH patients hospitalized for CHD tend to be older and contribute to a lower proportion of hospitalizations. Despite significant improvement in treatment, FH diagnosis and management remain sub-optimal, even in a founder population where FH represents a significant population burden. Funding Acknowledgement: Type of funding sources: None.